2017
DOI: 10.4315/0362-028x.jfp-16-516
|View full text |Cite
|
Sign up to set email alerts
|

Growth Kinetics of Listeria monocytogenes in Cut Produce

Abstract: Cut produce continues to constitute a significant portion of the fresh fruit and vegetables sold directly to consumers. As such, the safety of these items during storage, handling, and display remains a concern. Cut tomatoes, cut leafy greens, and cut melons, which have been studied in relation to their ability to support pathogen growth, have been specifically identified as needing temperature control for safety. Data are needed on the growth behavior of foodborne pathogens in other types of cut produce items… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 65 publications
0
24
0
Order By: Relevance
“…), green and red peppers and avocado pulp (Salazar et al . ). Studies such as these have outlined the importance of keeping produce at refrigeration temperatures to slow growth of L. monocytogenes populations, but have also demonstrated that postharvest, L. monocytogenes can survive on the surface of fresh produce for extended periods.…”
Section: Listeria Monocytogenes Survival On the Product Surface: Postmentioning
confidence: 97%
See 3 more Smart Citations
“…), green and red peppers and avocado pulp (Salazar et al . ). Studies such as these have outlined the importance of keeping produce at refrigeration temperatures to slow growth of L. monocytogenes populations, but have also demonstrated that postharvest, L. monocytogenes can survive on the surface of fresh produce for extended periods.…”
Section: Listeria Monocytogenes Survival On the Product Surface: Postmentioning
confidence: 97%
“…Conversely, L. monocytogenes can proliferate when in contact with a substrate such as cut produce (Salazar et al . ), but more research is needed to determine its growth behaviours specifically for fresh leafy produce. Additionally, more investigation is required to determine the effect that this change in environments has on the culturability and infectiveness of this pathogen.…”
Section: The Risk Posed From Soil Contaminated With L Monocytogenesmentioning
confidence: 99%
See 2 more Smart Citations
“…While there have been an abundance of studies to model bacterial survival kinetics (Chase et al, 2017, Salazar et al, 2017), transfer dynamics (Atwill et al, 2015), and preharvest risk factors (Pagadala et al, 2015) linked to raw produce consumption (Ibekwe et al, 2005; Pachepsky et al, 2016; Tian et al, 2012), relatively little is known about the potential risk inherent in agricultural water supplies.…”
mentioning
confidence: 99%